Design Of Information Flow For Handling Installation Issues Of Indihome At PT Telkom Akses Palu - Resti Widyastuti Hi. Husen; Asngadi Asngadi; Saharuddin Kaseng; Kadek Agus Dwiwijaya (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to redesign the information flow in handling installation-related obstacles for Indihome services at PT Telkom Akses Palu. Based on the obstacle data from October 2024 to February 2025, technical issues were the most dominant, followed by customer-related problems, while system-related issues were the least frequent. These findings indicate that most problems stem from suboptimal, fragmented, and non-integrated real-time information flow between departments. Using a descriptive qualitative method, this study analyzes the current system and identifies bottleneck points in the communication flow. The result is a proposed digital-based integrated information system design, emphasizing the role of the Helpdesk as a central coordinator. The system is expected to enhance the effectiveness, efficiency, and response speed in problem-solving and support digital transformation efforts within PT Telkom Akses Palu.